Occurrence of respiratory symptoms in elderly persons heard by the family health strategy in Águas Lindas, Ananindeua, Pará State - Renato da Costa Teixeira; Kézia Danniely da Silva Santos; Marinara do Socorro Dias da Silva; Valéria Marques Ferreira Normando; Madacilina de Melo Teixeira (Universidade Estadual de Maringá, 2020)
Respiratory diseases are among the five leading causes of death in Brazil, particularly among the elderly. This study identified the occurrence of respiratory symptoms in older persons. Specifically, a descriptive, observational, and quantitative study was conducted using a sample of elderly people enrolled in the Hypertension and Diabetes sessions of the Family Health Strategy program in a Brazilian city. MRC-ATS-DLD78 questionnaires were used to analyze respiratory symptoms with a sample comprised of 50 volunteers (mean age = 69.96 years). The median time living in a dwelling within a polluted sample area was 30 years, with 82% reporting spending more time per day at home or in the neighborhood. The presence of coughing was reported by 18% persons, expectoration (17%), productive cough (14%), wheezing (34%), dyspnea (12%), and respiratory diseases (26%). Physiological changes in aging associated with the effects of pollution exposure leave elderly people more vulnerable to respiratory diseases because they are predisposed to diseases, such as decreased pulmonary elasticity, elevated lung compliance, reduced oxygen diffusion capacity, reduced expiratory flow, and premature closure of airways. The occurrence of respiratory symptoms in the elderly was 30% with one symptom, two (22%), three (10%), four (6%), and five (2%).